2006
DOI: 10.1007/s00586-006-0270-1
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant fracture of bilateral occipital condyle and inferior clivus: what is the mechanism of injury?

Abstract: With the routine use of multi-slice high resolution computed tomography, increasing number of occipital condyle fractures have been reported in the last decade. The authors report a very rare case of bilateral occipital condyle fracture complicated by the fracture of the inferior clivus and discuss the possible mechanisms of injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 12 publications
0
18
0
3
Order By: Relevance
“…44 Oblique CF 24 and transverse CF 14 resulting from occipital fracture extension have also been described in the literature, with a further 4 cases describing CF with associated occipital fracture. 5,8,17,45 Interestingly, ISS and proportion of MVAs increased from hairline, to linear, to diastatic and finally to displaced CF type. It is clear that these fractures result from high-impact trauma, and previous authors have demonstrated forces of 4300 N required to produce fractures of the skull base.…”
Section: Subtypes and Pathogenesis Of Cfmentioning
confidence: 99%
“…44 Oblique CF 24 and transverse CF 14 resulting from occipital fracture extension have also been described in the literature, with a further 4 cases describing CF with associated occipital fracture. 5,8,17,45 Interestingly, ISS and proportion of MVAs increased from hairline, to linear, to diastatic and finally to displaced CF type. It is clear that these fractures result from high-impact trauma, and previous authors have demonstrated forces of 4300 N required to produce fractures of the skull base.…”
Section: Subtypes and Pathogenesis Of Cfmentioning
confidence: 99%
“…[1,4,6] AOİ bulunmayan iki taraflı OKK olguları benzer şekilde stabil olarak kabul edilerek servikal eksternal immobolizasyon tedavi edilebilir. [2,9] Bununla birlikte, Dashti ve ark., [10] inferior klivus kırığının eşlik ettiği iki taraflı OKK olan çoklutravmalı bir olguda Halo yelek kullanı-mı ile kemik iyileşmenin sağlandığını bildirmişlerdir. OKK'ya AOİ'nin eşlik etme riski %9.7'dir (Mueller ve ark.).…”
Section: Discussionunclassified
“…49,50 They are typically the result of highvelocity trauma and are often associated with fatal mechanisms. 51,52 Static loading forces produce typical traumatic diastasis in the clivus. 53…”
Section: ■ ■ Clivus Fracturesmentioning
confidence: 99%